P-257 Recruiting graduate talent in the hospice sector – a case study. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Veronesi, Megan; Glover, James
Abstract : Background : Recruiting and retaining qualified and competent staff is one of the biggest challenges facing many hospices. There is a relatively untapped pool of highly qualified graduates who want to work in the charity sector however hospices are not on the radar for many. They may assume hospices are NHS organisations; that all jobs are clinical; or that working in death and dying is depressing. As local charities, hospices do not have the resources to run their own graduate schemes to challenge these perceptions. Aims: To attract highly qualified and competent staff To meet an identified skills gap To see an immediate return on our investment. Methods: We assessed our skills gap and developed a role description. We approached Charityworks, the leading UK non-profit graduate programme, to source us a graduate who met the criteria. The programme offers a nationwide recruitment campaign, a rigorous selection process, and ongoing development for the graduate over their 12 month placement. In 2014 we became the first hospice to host a Charityworks graduate trainee. Results: We have now hosted two graduates, one in a project management role and another in a communications role. Both graduates: have first class honours degrees (in Civil Engineering and in Law) from leading universities came with relevant skills and experience, in project and data management and in media management respectively had a swift and positive impact. Our first graduate's environmental sustainability project became organisational policy. Within 6 months, our second graduate contributed significantly towards our communications objectives, increasing Facebook likes by 30% and Instagram followers by 115%. Conclusions : Charityworks gave us access to a higher level of talent than we could have attracted individually, at a fraction of the cost of running a comparable scheme ourselves. We would encourage all hospices to tap into the pool of talented graduates available to them through the Charityworks scheme.